READING HABIT DAN READING PREFERENCES MAHASISWA JURUSAN TEKNIK MESIN TAHUN 2015/2016 POLITEKNIK NEGERI UJUNG PANDANG - Sahriana Sitti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
There are four skills in English, namely listening, speaking, reading and writing. Reading as one of the skills in teaching English plays important roles in English. This research aims to find out the reading habit, the reading techniques known and used by the students and the problems facing by the students of Politeknik Negeri Ujung Pandang in reading comprehension. The population of the research is the students of Mechanical Engineering Department of Politeknik Negeri Ujung Pandang. While the samples of the research are the D4 Manufacturing Engineering and D4 Mechatronics Engineering students. The total number of the students is 45. The method used in this research is qualitative descriptive analysis. This method is used as a procedure to solve the problems which are observed. To get the data for the research, a questionnaire is used to find out the reading habit, the reading techniques and the problems faced by the students. The questionnaire comes in form of semi-open-ended where besides providing some options for each number; the students are also given a chance to give their own answer or opinion.